Exploring the Customer’s Insight of Hygiene Compliance During Distribution Process to the Store - Harun, Nor Sabrina; Md. Sapry, Hairul Rizad; Ahmad, Abd Rahman; Ali Thabah, Asep (Springer, 2024)
The study is exploring the customer’s insight into the hygiene compliance of Gardenia products during the distribution process to the store. In the COVID-19 era, people are concerned about the hygiene of their food. Even though there is no strong evidence that the virus of COVID-19 could spread through food, the hygiene of the food is still a concern among consumers. The objective of this study is to examine consumer insight into hygiene compliance through the logistics perspective. Four hypotheses were developed based on the logistics-related element of the distribution of Gardenia products, which are packaging, food storage, handling process, and distribution process itself. The researcher chooses quantitative methods that rely on the use of Google Forms to collect feedback from the respondent. The study managed to collect 80 pieces of feedback from the respondents and analyzed the data using the structured equation modeling (SEM) approach. The results revealed a significant relationship between those logistics elements to the hygiene compliance which provide new insight to the practitioner in developing a comprehensive strategy for convincing the consumer of the quality of their product. It also contributes a new finding to the field of study which was previously more focused on the material and the food process only.